The influence of solution choice on fluid resuscitation in patients with septic shock - Zuo, Tinglan; Solyarik, Sergey (ScienceRise: Medical Science, 2021)
The aim. Compare the hemodynamic effects and safety of infusion of the balanced crystalloid solution, sorbitol-based solution, and standard solution (0.9 % sodium chloride). Materials and methods. A prospective randomized clinical trial was carried out, the study included 68 adult patients, who had the active surgical infection, and were in a state of septic shock. A corresponding solution with a volume of 500 ml was used for resuscitation. Hemodynamic and other clinical and laboratory parameters were monitored. Results. There was no significant difference in mean arterial pressure (MAP) between the 3 groups before the 45th minute (p>0.05), from the 50th minute to 2 hours they were found only between the NS and Sorb groups (p <0.05). No statistically significant difference in heart rate (HR) was obtained in any measurement (p> 0.05). Cardiac output (CO) and oxygen delivery (DO2) did not differ until 35 min (p> 0.05) and up to 40 min (p> 0.05); after 40 min and 45 min, a significant difference was also found between the Sorb and NS groups (p <0.05). After infusion of a sorbitol-containing solution and a balanced polyionic solution, the acid-base state of the blood significantly improved. The applied dose of the sorbitol-containing solution was safe for renal function and blood clotting in septic shock in this study. But the applied balanced polyionic solution may be associated with a decrease in the number of platelets. Daily changes by APACHE II scores in each group were not statistically significant. The difference in 7-day and 28-day mortality between groups was not statistically significant (p>0.05). Conclusions. In our study, the balanced polyionic solution with 1.9 % sodium lactate and 6 % sorbitol was the most effective and safe infusion solution for the treatment of septic shock, it can be used as a supplement to balanced crystalloid solutions. When using a balanced polyionic solution (Ringer's acetate) with 0.07 % L-malonic acid, the platelet count should be monitored more often